1992
DOI: 10.1111/j.1365-2249.1992.tb07954.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in circuIating B cells and immunoglobulin cIasses and subcIasses in a healthy aged popuIation

Abstract: SUMMARYThe study of 87 adulls of different ages, including 15 centenarians, selected for their heallhy status, showed Ihal profound changes of humoral immunity occur throughout life. In particular, a statislically significant age-related increase ofthe serum level of immunoglohulin classes (IgG and IgA but not IgM) and IgG subclasses (IgGI, 2 and 3, but not IgG4) was detected. A parallel agerelated decrease of circulating B eeils was also observed. The hypothesis ofa complex derangement of Bcell funetion and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(51 citation statements)
references
References 18 publications
6
44
0
1
Order By: Relevance
“…This finding was however restricted to subjects with no history of previous exposure to this vaccine (Gibson et al, 2012) suggesting that the influence of increasing fruit and vegetable intake may target naïve B cells rather than antigen experienced memory B cells. This finding may be related to the observation that serum levels of IgG2 increase with age, and that IgG2 is produced against polysaccharide antigens required for defence against bacteria such as pneumococci (Paganelli et al, 1992).…”
Section: Carotenoidsmentioning
confidence: 91%
“…This finding was however restricted to subjects with no history of previous exposure to this vaccine (Gibson et al, 2012) suggesting that the influence of increasing fruit and vegetable intake may target naïve B cells rather than antigen experienced memory B cells. This finding may be related to the observation that serum levels of IgG2 increase with age, and that IgG2 is produced against polysaccharide antigens required for defence against bacteria such as pneumococci (Paganelli et al, 1992).…”
Section: Carotenoidsmentioning
confidence: 91%
“…This is in agreement with previous data that have demonstrated a reduction of IgM ''only'' memory B cells in the elderly (Shi et al 2005). We show a slight increase in the expression of IgG and IgA on switched memory B cells but this did not reach significance, although the relative proportions of the different isotypes of memory cells mirrors the relative proportion of serum immunoglobulin of the different isotypes (Paganelli et al 1992;Listì et al 2006).…”
Section: Surface Immunoglobulin Of Dn Cellsmentioning
confidence: 91%
“…In contrast to mouse model, in humans there is a decrease both in percentage and absolute number of total CD19 + B lymphocytes (Veneri et al, 2009;Faria et al, 2008;Frasca et al, 2008;Shi et al, 2005;Chong et al, 2005;Colonna Romano et al, 2003Breitbart et al, 2002;Huppert et al, 1998;Wikby et al, 1994;Paganelli et al, 1992). Moreover, it has been demonstrated that absolute number of B cell precursors in the bone marrow declines with age and particularly during adolescence (McKenna et al, 2001), however, B lymphopoiesis persists throughout adult life (Rossi et al, 2003).…”
Section: B Lymphocytesmentioning
confidence: 99%